2004
DOI: 10.1002/chin.200409297
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Catalytic Technology for the Manufacture of CF3I

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Gas-phase reactions of halon 1301 with hydrogen, CH4 and C3H8 have been investigated recently by Li et al (8,9) and Yu et al (10). They have reported that hydrodehalogenation of halon 1301 with H2 or CH4 is a promising process for production of CHF3, which can be used as the precursor for production of CF3I (11), a replacement for halon 1301.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase reactions of halon 1301 with hydrogen, CH4 and C3H8 have been investigated recently by Li et al (8,9) and Yu et al (10). They have reported that hydrodehalogenation of halon 1301 with H2 or CH4 is a promising process for production of CHF3, which can be used as the precursor for production of CF3I (11), a replacement for halon 1301.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively small number of studies on the gas-phase hydrodehalogenation of halons have been reported. [2][3][4][5][6][7] For example, Li et al studied the gas-phase hydrodehalogenation of CBrF 3 (halon 1301) with hydrogen and methane 3,4 and found that these reactions can be used to produce CHF 3 , a precursor for the synthesis of CF 3 I, 8 a promising halon replacement chemical.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this finding is that a process has been developed in which CHF 3 is converted to CF 3 I (also known as halon 13001). 7 CF 3 I is a chemically active fire suppressant that is being considered as a replacement for halon 1301, although because of occupational exposure problems, there is significant resistance to adopting CF 3 I as a flooding agent. [8][9] For this reason, it is generally considered for use only in unoccupied spaces.…”
Section: Introductionmentioning
confidence: 99%
“…10 The process for conversion of CHF 3 to CF 3 I, developed by Nagasaki et al, involves the catalytic reaction of CHF 3 with I 2 . 7 Nagasaki and his co-investigators argue that the reaction proceeds via the formation of a surface carbene (CF 2 :) species, also resulting in the generation of HF. The carbene then disproportionates to carbon and CF 3 , which rapidly produces CF 3 I.…”
Section: Introductionmentioning
confidence: 99%